2021
DOI: 10.1021/acsnano.1c08108
|View full text |Cite
|
Sign up to set email alerts
|

Complementing Cancer Photodynamic Therapy with Ferroptosis through Iron Oxide Loaded Porphyrin-Grafted Lipid Nanoparticles

Abstract: Nanomaterials that combine multimodality imaging and therapeutic functions within a single nanoplatform have drawn extensive attention for molecular medicines and biological applications. Herein, we report a theranostic nanoplatform based on a relatively smaller (<20 nm) iron oxide loaded porphyrin-grafted lipid nanoparticles (Fe3O4@PGL NPs). The amphiphilic PGL easily self-assembled on the hydrophobic exterior surface of ultrasmall Fe3O4 NPs, resulting in a final ultrasmall Fe3O4@PGL NPs with diameter of ∼10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 50 publications
3
66
0
Order By: Relevance
“…which is conducive to accurate tumor diagnosis and can guide the selection of time windows and real-time monitoring during cancer therapy. 45,46 Therefore, MR imaging results were similar to fluorescence imaging results, both in vitro and in vivo, suggesting that B. bifidum-mediated PFH@CL/Fe 3 O 4 NPs can be retained in tumors and be used as a contrast agent for T2-weighted MRI. Bio-targeted nanoplatforms combined with B. bifidum and PFH@CL/Fe 3 O 4 NPs can provide guidance and monitoring during HIFU therapy.…”
supporting
confidence: 61%
“…which is conducive to accurate tumor diagnosis and can guide the selection of time windows and real-time monitoring during cancer therapy. 45,46 Therefore, MR imaging results were similar to fluorescence imaging results, both in vitro and in vivo, suggesting that B. bifidum-mediated PFH@CL/Fe 3 O 4 NPs can be retained in tumors and be used as a contrast agent for T2-weighted MRI. Bio-targeted nanoplatforms combined with B. bifidum and PFH@CL/Fe 3 O 4 NPs can provide guidance and monitoring during HIFU therapy.…”
supporting
confidence: 61%
“…After conjugation with carboxyphenylboronic acid (CPBA), the improved internalization of the Au@Chl-Fe nanorods enabled PDT and restricted cell growth upon exposure to 660 and 785 nm light irradiation at extremely low concentrations of 0.16–1.6 ppm [Au] compared to other Au-related therapeutics. The previous development of NIR-PDT in BC required the integration of upconversion NPs as a NIR-to-visible light transducer. Importantly, NIR light can drive better tissue-penetrating treatment due to the low absorption cross section and scattering. ,, Although combining CDT and PDT will result in strong ROS induction and better therapeutic outcomes, ,,, it remains unclear how to properly combine the two strategies using one functional material with high biocompatibility and specificity to BC. Our demonstration showed that the enhanced inhibition of BC cell growth by direct NIR light-induced PDT prior to a long CDT period caused the immediate consumption of GSH antioxidant molecules and induced membrane lipid peroxidation (Scheme b), thus exacerbating ferroptosis in BC cells and raising hope for a cure for BC. Such a low treatment dose is advantageous for reducing the risk of metal accumulation in the body.…”
Section: Introductionmentioning
confidence: 90%
“…Inspired by Chl construction in the chloroplast for enhanced synergic photosynthesis, Au nanoparticles assembled with a high density of Chl were developed to increase the photoproduction of 1 O 2 to combat malignant tumor lesions. Herein, iron chlorophyll (Chl-Fe), acting as a natural photosensitizer and chemodynamic ferroptosis therapy (CDT) activator, was used for the surfactant-free green synthesis of Au@Chl-Fe nanomaterials. Compared to previously reported spherical Au nanoparticles synthesized by surfactant additive and plant extract biomaterial coating methods, our current green synthesis involving J-aggregates of Chl-Fe for the shape-guided growth of Au nanocrystals led to the formation of Au@Chl-Fe nanorod composites (Scheme a) with controlled temperatures, concentrations, and Chl-metal species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some nanoparticles are also ideal carriers for traditional photosensitizers ( Lucky et al, 2015 ; Xie et al, 2021 ). The nano-photosensitizers and nano-delivery systems are able to accumulate more efficiently in tumor tissue through the enhanced permeability and retention (EPR) effect owing to the particle size and the abnormal vascular structure of tumors ( Peer et al, 2007 ; Hao et al, 2020 ; Li et al, 2021b ; Liang et al, 2021b ). The nanomaterials can also be further modified or functionalized to improve the targeting efficacy, enhancing the dosage of in tumor and reducing toxicity to normal tissues ( Zhong et al, 2015 ; Seidi et al, 2018 ; Liang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%